Marketing Solutions in Rural Tourism Development in Lithuania - Ramanauskienė, Jadvyga; Ramanauskas, Julius; Gargasas, Audrius (Ekonomika, 2006)
In the contemporary world, an increasing number of enterprises, including rural tourism businesses, employ marketing methods and knowledge in their activities. Rural tourism has an exclusive link with nature. For this reason its services became very popular. Its development is furthered by the right marketing system and an expedient EU and national support. Rural tourism becomes a new field of activities, which makes good income and returns in rural areas and enables to change from agricultural production to service trade. It is an extra income for farmers or other agrarian people. In addition, rural tourism provides social and cultural benefits, i.e. social contacts between local population and tourists, an augmented perception of the importance and preservation of cultural heritage, stronger communication among local people. Local communities are able to develop economics in the area, to improve living standards and to preserve cultural heritage and social values. Therefore, rural tourism development, preconditioning improvement of living standards of tourists and local people, increasingly becomes an object of scientific and practical discussions. In the article, the authors analysers rural tourism development, reveal its problems and marketing tasks. The aim of the study was to formulate the measures of improving the marketing solutions in rural tourism development.